Cultural responsive pedagogy in English and eliminating the achievement gap - Coffey, Wyndemere (My University, 2008)
This project investigates the causes of academic achievement gap, overviews the best practice solutions, and demonstrates how the author uses Culturally Responsive Pedagogy in her English classroom to elimate the achievement gap.
Plan B Paper. 2008. Master's of Science in Secondary Education--University of Wisconsin-River Falls. English Department. 20 leaves + Hip Hop/Classics Unit Plan ([31]leaves).
Keywords: Race awareness; Multiculturalism; Poetry--Study and teaching (Secondary); Achivement gap in education; Multicultural education; Minorites--Education; Hip-hop; English language--Composition and exercises--Study and teaching; Culturally responsive pedagogy; Hip-hop--Poetry; Language arts (Secondary); Hip-hop--Study and teaching; Curriculum planning